2018
DOI: 10.1111/pce.13372
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid negatively modulates plant defence against rice black‐streaked dwarf virus infection by suppressing the jasmonate pathway and regulating reactive oxygen species levels in rice

Abstract: Abscisic acid (ABA) plays a multifaceted role in plant immunity and can either increase resistance or increase susceptibility to some bacterial and fungal pathogens depending on the pathosystem. ABA is also known to mediate plant defence to some viruses. In this study, the relationship between the ABA pathway and rice black-streaked dwarf virus (RBSDV) was investigated in rice. The expression of ABA pathway genes was significantly reduced upon RBSDV infection. Application of exogenous hormones and various ABA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 62 publications
(102 reference statements)
4
57
0
1
Order By: Relevance
“…However, ROS were shown to play vital roles in plant defence against rice viruses (Wu et al , ). Our previous results also showed that high basal ROS levels can enhance antiviral defence against RBSDV infection (Xie et al , ). Here, our results indicate that auxin can induce the expression of OsRboh and that disruption of auxin signalling decreased the expression of OsRboh .…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…However, ROS were shown to play vital roles in plant defence against rice viruses (Wu et al , ). Our previous results also showed that high basal ROS levels can enhance antiviral defence against RBSDV infection (Xie et al , ). Here, our results indicate that auxin can induce the expression of OsRboh and that disruption of auxin signalling decreased the expression of OsRboh .…”
Section: Discussionsupporting
confidence: 56%
“…It has recently been reported that accumulation of basal ROS plays an important role in antiviral immunity (Wu et al , ; Xie et al , ). In plants, NADPH oxidases (respiratory burst oxidase homologs, Rboh ) play key roles in generating ROS by catalysing the conversion of O 2 to superoxide (O 2 ‐ ) (Suzuki et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, during RBSDV infection in rice, jasmonic acid (JA) production was found to be increased; whereas, brassinosteroid (BR) production, which is important for integrating salicylic acid (SA) pathway with jasmonic acid (JA) pathway, was suppressed (He et al 2017;Pan et al 2018). A recent study further showed that abscisic acid (ABA) could negatively regulate rice resistance to RBSDV infection (Xie et al, 2018).…”
Section: Introductionmentioning
confidence: 99%